The G1 phase E3 ubiquitin ligase TRUSS that gets deregulated in human cancers is a novel substrate of the S-phase E3 ubiquitin ligase Skp2 - Jamal, Azfar (Cell Cycle, 2015)
E3 ubiquitin ligases have been implicated in the ubiquitination and proteasome-mediated degradation of several key regulators of cell cycle. Owing to their pleotropic behavior, E3 ubiquitin ligases are tightly regulated both at transcriptional and post-translational levels. The E3 ubiquitin ligase TRUSS (tumor necrosis factor receptor-associated ubiquitous scaffolding and signaling protein) which negatively regulates c-Myc, are found down-regulated in most human cancer cell lines. However, the mechanism of regulation of intracellular levels of TRUSS remains elusive. Here we show that TRUSS is expressed majorly during the G1 phase of cell cycle and its level starts to decline with the expression of S-phase specific E3 ligase Skp2. Enforced expression of Skp2 led to a marked increase in the ubiquitination of TRUSS after its phosphorylation by GSK3β and followed by rapid proteolytic degradation. Our co-immunoprecipitation studies suggested a direct interaction between Skp2 and TRUSS through the LRR motif of Skp2. Interestingly, the human tumor samples that exhibited elevated expression of Skp2, showed relatively poor expression of TRUSS. Further, enforced expression of HBx, the oncoprotein of Hepatitis B virus which is known to stabilize c-Myc and enhance its oncogenic potential, led to the intracellular accumulation of TRUSS as well as c-Myc. Apparently, HBx also interacted with TRUSS which negatively impacted the TRUSS-c-Myc and TRUSS-Skp2 interactions leading to stabilization of TRUSS. Thus, the present study suggests that TRUSS is a novel substrate of E3 ligase Skp2 and that disruption of TRUSS-Skp2 interaction by viral oncoproteins could lead to pathophysiological sequelae.